Peran Guru dalam Penerapan Projek Penguatan Profil Pelajar Pancasila terhadap Budaya Positif di Sekolah Dasar Negeri 241 Palembang - Firdiansyah, Firdiansyah; Ahyani, Nur; Mahasir, Mahasir (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research examines the role of teachers in implementing a project to strengthen students' Pancasila profiles towards fostering a positive culture at SD Negeri 241 Palembang. The research aims to explore how teachers contribute to shaping students' understanding and realization of Pancasila values, thus encouraging the creation of a positive cultural environment in schools. Through qualitative methods, including interviews and observations, this research examines teachers' strategies, the challenges they face, and their impact on student attitudes and behavior. The findings show that teachers play an important role in instilling Pancasila values, influencing students' cultural perceptions, and fostering a conducive learning atmosphere in line with national ethos and moral values. This research underlines the importance of teacher involvement in character education and its implications in creating a harmonious school environment that is rooted in Indonesian cultural values.